Projeto tutoria: elemento mobilizador para a formação contínua de professores e superação do fracasso escolar na escola pública - Torres, Bianca dos Santos (2012)
In 2009, the EE Clarice Lispector forward to finding a high rate ofstudents retained at the end of EF II, implemented a project called Project Mentoring as a pedagogical alternative for overcomingschool failure, since the teachers through this -tutors carry out actions to support, monitoring and guidance to students about his life and socio-emotional school, seeking the full development of thatstudent. The tutor-teacher becomes a facilitator of teaching and learning and an organizer of the Political Pedagogical Project(PPP), actions that aim to build the permanence and qualityeducation to the student. Therefore, this study aimed to investigate the process ofdeployment and implementation of the Tutoring Project in the years 2009-2011, its challenges and impacts on school culture,considering it as a mobilizing element for the training of teachers involved and overcoming school failure in a public basic education.It was intended to develop a qualitative research, containing the results of the dialogues studied subjects, as well as literature andanalysis of documents produced by the school community. Throughdata analysis, we consider that the Mentoring Project for the hostcollaborates with students, building a sense of belonging to theschool unit, with a view to overcoming school failure, leading to the same chances of success in your personal life and school. We observed that the project has contributed to significant changes in teachers' action-tutors, making it an integral part of school culture